Effectiveness of Role-Play in Improving Communication Skills: Evidence from University Students of Hospitality Studies (The Batuk, 2026)
Role play is increasingly used as a teaching strategy to enhance communication skills in higher education; however, empirical evidence from hospitality education in Nepal remains lacking. This study examines students' perceptions towards role play and its effectiveness in enhancing their communication skills. A quantitative cross-sectional design was employed, and data were collected from 40 undergraduate students, equally distributed by year of study (60% first year, 40% second year) as they are involved in hospitality practical sessions where role play is conducted. A structured 7-point Likert scale questionnaire was administered to measure students’ perception and perceived communication outcomes. Descriptive analysis revealed students’ positive perception towards role play experience, with a mean score of 5.10. Further, correlation analysis found statistically significant positive relationships between role play and communication variables, with coefficients ranging from .577 to .808. The findings suggest that role play is perceived as an effective instructional strategy for improving communication confidence, pronunciation, and clarity of expression. The study offers practical implications for hospitality educators and contributes institution level empirical evidence to the literature.